Online characterization of planetary surfaces: PlanetServer, an open-source analysis and visualization tool. (January 2018) - Marco Figuera, R.; Pham Huu, B.; Rossi, A.P.; Minin, M.; Flahaut, J.; Halder, A.
Abstract: The lack of open-source tools for hyperspectral data visualization and analysis creates a demand for new tools. In this paper we present the new PlanetServer, a set of tools comprising a web Geographic Information System (GIS) and a recently developed Python Application Programming Interface (API) capable of visualizing and analyzing a wide variety of hyperspectral data from different planetary bodies. Current WebGIS open-source tools are evaluated in order to give an overview and contextualize how PlanetServer can help in this matters. The web client is thoroughly described as well as the datasets available in PlanetServer. Also, the Python API is described and exposed the reason of its development. Two different examples of mineral characterization of different hydrosilicates such as chlorites, prehnites and kaolinites in the Nili Fossae area on Mars are presented. As the obtained results show positive outcome in hyperspectral analysis and visualization compared to previous literature, we suggest using the PlanetServer approach for such investigations. Highlights: An open-source tool (WebGIS and Python API) for hyperspectral analysis and visualization. The Web Coverage Processing Service (WCPS) OGC standard is used to pursue RGB combinations and Spectral profiles. The tool can be adapted to work with other hyperspectral datasets.